Second and fourth order spin-lattice coefficients for Gd 3+ in theoria. - Oseroff, S. B.; Calvo, R.; Fainstein, C. (American Chemical Society, 1970)
Fil: Oseroff, S. B. Comisión Nacional de Energía Atómica; Argentina